Feasibility Analysis of the Home-Based Tofu Industry in Bangunsari Village, Lasalepa District, Muna Regency (Case Study on Bina Mandiri Tofu Business) - Ayuh'mun, Sri Wulan; Abdi; Gafarudin, Abdul (International journal of technology and education research, 2025)
This study aims to determine the feasibility of a household tofu industry business in Bangunsari Village, Lasalepa District, Muna Regency with a case study on the Bina Mandiri tofu business. This study was conducted in October 2024 - April 2025 and data collection was in March - April 2025. This study uses a case study method with a quantitative descriptive approach. Data analysis includes the calculation of fixed costs, variable costs, revenue, profit, and business feasibility indicators such as Return Cost Ratio (R/C), Return on Investment (ROI), and Break Even Point (BEP). The results of this study indicate that this business is profitable with a total profit of IDR 56,798,146/month, while the value of business feasibility is shown through the results of financial analysis with an R/C Ratio value of IDR 2.29, an ROI value of 12.9%, and a BEP value obtained by BEP units of 2.19 kg, BEP production of IDR 131,854. This shows that this tofu business is feasible to be developed